PHYTOCHEMICAL SCREENING OF THREE BATAK LEEKS VARIANS (A. chinense G. Don) - Aliyah Fahmi (JURNAL KIMIA MULAWARMAN, 2021)
"Phytochemical screening of Three Batak Leeks (A. chinense G. Don) Varians " has been carried out. For phytochemical screening, secondary metabolites were analyzed, including alkaloids, phenolics, flavonoids, terpenoids, steroids and saponins. From the three samples of Batak Leeks (fresh, dried and methanol extract), the result was concluded that secondary metabolites of the terpenoids were weak in the methanol extract and not detected in the fresh and dried Batak leeks .